Prognostic utility of neutrophil gelatinase-associated lipocalin (NGAL) levels for cardiovascular events in patients with stable coronary artery disease treated with percutaneous coronary intervention: a prospective longitudinal cohort study - Ting-Yu Lin; Hsin-Bang Leu; Yen-Wen Wu; Wei-Kung Tseng; Tsung-Hsien Lin; Hung-I Yeh; Kuan-Cheng Chang; Ji-Hung Wang; Wei-Hsian Yin; Chau-Chung Wu; Chun-Yao Huang; Shing-Jong Lin; et al. (Biomarker Research)
Abstract Introduction Neutrophil gelatinase-associated lipocalin (NGAL) modulates the enzymatic activity of matrix metalloproteinase-9, which is an important mediator of plaque instability in atherosclerosis. High NGAL levels can independently predict all-cause mortality and major adverse cardiac events (MACE) in patients with acute myocardial infarction (AMI). However, studies that have measured NGAL levels in patients with stable coronary artery disease (CAD) are limited. Furthermore, no significant prognostic predictive value between NGAL levels and stable CAD has been established. Hypothesis We aimed to investigate the prognostic role of NGAL levels in a prospective cohort study of patients with stable CAD treated with percutaneous coronary intervention (PCI). Methods A total of 2,238 stable patients with CAD and a previous PCI were enrolled in a multicenter prospective observational study (The National Taiwan Biosignature Research, NTBR) in Taiwan. The primary outcome was the occurrence of MACE (cardiovascular death, nonfatal myocardial infarction, and ischemic stroke). The secondary outcome was a composite of cardiovascular events (cardiovascular death, nonfatal MI, nonfatal stroke, and hospitalization for heart failure). Results During the mean follow-up period of 4.6 ± 1.7 years, 441 patients reached the primary endpoints. Kaplan-Meier analysis showed that event-free survival was significantly different between the first and third tertile groups (log-rank test, p < 0.001) in subjects categorized by NGAL levels. In a multivariate Cox proportional hazard regression analysis, plasma NGAL levels were independently associated with an increased risk of MACE [adjusted hazard ratio (aHR) = 1.35; 95% confidence interval (CI) = 1.18–1.54, p < 0.001], AMI (aHR = 1.34; 95% CI = 1.12–1.59, p < 0.001), and target vessel revascularization (aHR = 1.35; 95% CI = 1.19–1.53, p < 0.001). Addition of serum NGAL levels to the traditional risk model improved its prediction value for future cardiovascular events. Conclusions High plasma NGAL levels were independently associated with the occurrence of MACE and composite cardiovascular events in patients with stable PCI-treat CAD.